National Geographic: visual and verbal representations of subaltern cultures revisited - Mizan, Souzana (2011)
This thesis is a multidisciplinary endeavor that draws on theories from Visual Culture Studies, Subaltern Studies and Critical Theory. The discourses of these areas interact in various ways in order to analyze representations of subaltern groups in National Geographic magazine. We see these representations as multimodal cultural texts that mobilize historical, sociological, political, economic, aesthetic and philosophical elements. We do close reading of the visual and verbal texts that the magazine produces on the subaltern in order to show that we get to know more about the Western conceptual world through these representations than on the Other since the conceptual categories National Geographic uses are culture specific and not universal. We show that both the discourse of the magazine and that of the researcher doing the analysis are products of their locus of enunciation and its historical context. We finally emphasize the importance of admitting the power of mediation when we talk about anthropological representations. The magazine uses an apparently scientific discourse in order to validate the truthfulness of its representations. However, its science is formed by concepts expressive of the Western cultural hegemony which seeks to construct knowledge that is rooted in power.